Evaluation of anti-inflammatory activity of ethanolic whole plant extract of Desmodium gangeticum L. - Nusrath Yasmeen; K Sujatha (International Journal of Phytomedicine, 2013)
The present study was designed to investigate the anti-inflammatory activity of the ethanolic extract of whole plant of Desmodium gangeticum. Investigations were done by Carrageenan-induced paw oedema method in rats. Here the extract at the 100 & 200mg/kg dose level showed 36.68% (p<0.001) inhibition of edema volume at the end of 4hr .The extract reduced significantly the formation of oedema induced by carrageenan. Inflammatory diseases including different types of rheumatic diseases are very common throughout the world. Therefore the search for a better tolerated anti-inflammatory agent appears to be a necessity. Desmodium gangeticum is used as a folk medicine for the treatment of inflammation in India. Present study revealed that the plant Desmodium gangeticum possesses a significant anti-inflammatory activity as evidenced in carrageenan induced paw edema method, which supports the folkloric claim of the anti-inflammatory activity of the plant.